2006
DOI: 10.1002/ijc.22094
|View full text |Cite
|
Sign up to set email alerts
|

Variant genotypes of CDKN1A and CDKN1B are associated with an increased risk of breast cancer in Chinese women

Abstract: p21Cip1 and p27 Kip1 are cyclin-dependent kinase inhibitors, which can arrest cell proliferation and serve as tumor suppressors. Reduced protein expression of p21Cip1 and p27 Kip1 was frequently observed in a subset of cancers, including breast cancer. In this study, we hypothesized that genetic variants in CDKN1A (encode for p21 Cip1) and CDKN1B (encode for p27 Kip1 ) may modulate the risk of breast cancer. To test this hypothesis, we evaluated the associations of the polymorphisms of Ser31Arg and C120T in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…Among these, 11 publications appeared to meet the inclusion criteria and were subjected to a detailed full-text review. [12][13][14][15][16][17][18][19][20][21][22] We further excluded three publications because they did not provide detailed genotype data of cases and controls. 18,20,22 Therefore, our final data pooling consisted of eight publications (Table 1).…”
Section: Meta-analyses Databasementioning
confidence: 99%
See 2 more Smart Citations
“…Among these, 11 publications appeared to meet the inclusion criteria and were subjected to a detailed full-text review. [12][13][14][15][16][17][18][19][20][21][22] We further excluded three publications because they did not provide detailed genotype data of cases and controls. 18,20,22 Therefore, our final data pooling consisted of eight publications (Table 1).…”
Section: Meta-analyses Databasementioning
confidence: 99%
“…18,20,22 Therefore, our final data pooling consisted of eight publications (Table 1). [12][13][14][15][16][17]19,21 Three of the eight case-control studies were conducted in Caucasians, and the remaining five studies were conducted in Asians. Overall, there were four breast cancer studies, two prostate cancer studies, one pancreatic cancer study, and one oral squamous cell cancer study.…”
Section: Meta-analyses Databasementioning
confidence: 99%
See 1 more Smart Citation
“…The risk of breast cancer is raised about two fold in the affected Saudi women. Several studies have identified an association with SNPs and breast cancer in the Chinese population (Ma et al, 2006). It has been proposed that different genetic backgrounds due to the combination of environmental could explain the remaining familial breast cancer risk (Pharoah et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…SNPs on 2q35 (rs13387042) and 5p12 (rs4415084 and rs10941679) have been shown to be associated with estrogen-receptor (ER) positive breast cancer [5,6] and SNPs lying within cell cycle genes have been shown to be associated with breast cancer in the British population (rs997669 in CCNE1, rs3176336 in CDKN1A, rs34330 in CDKN1B and rs3731239 in CDKN2A/2B) [7]. These associations have yet to be confirmed in other studies or populations, with the exception of rs34330, which has been shown to be associated with breast cancer in the Chinese population [8].…”
Section: Introductionmentioning
confidence: 99%